การศึกษาการเตรียมความพร้อมในการดำเนินการ ตามนโยบายปฏิรูปการศึกษาของโรงเรียนประถมศึกษา สังกัดสำนักงานการประถมศึกษาจังหวัดฉะเชิงเทรา - สมพักร์ สันติพงศ์ศักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The propose of this research was to study the readiness preparation for the implementation of the educational reform policy of elementary schools under the office of Chachoengsao provincial primary education. Samples were 175 administrators and 351 teachers in elementary schools under the office of Chachoengsao provincial primary education. Research instruments were interviewing forms and questionnaires. Data were analysed by frequency and percent. Research findings were as follows : 1. According to the Curriculum Reform ; most schools prepared by studying the curriculum, establishing the teachers meeting, setting the team for curriculum development, and the committee for curriculum evaluation. 2. According to the Teaching and Learning Process Reform ; most schools prepared by setting up the teachers meeting, sending teachers to attend the workshop, encourage teachers to produce classroom research and emphasis in childcentre approach. 3. According to the Teaching Profession Reform : most schools prepared by encouraging teachers to attend seminar, establishing understanding according to teaching profession standard, attending work-shop, providing academic work, and produce classroom research. 4. According to Administrative and Management Reform ; most schools prepare for the School - Base Management, involving community in school management, developing educational quality, and preparing for school quality evaluation